Chloroquine accumulation in Plasmodium falciparum isolated digestive vacuoles - Saliba, Kevin John (Division of Clinical Pharmacology, 2017)
Due to the development of drug-resistance by Plasmodium falciparum, the utilisation of chloroquine, a cheap and effective antimalarial has become limited. The mechanism of chloroquine-resistance is, at best, unresolved. This thesis describes an investigation of chloroquine accumulation in pure and intact Plasmodium falciparum isolated digestive vacuoles, the site of chloroquine accumulation and action. Marker enzymes and gel electrophoresis were used to demonstrate purity, and electron microscopy to verify integrity of isolated vacuoles. Using this method, vacuoles were isolated in a yield high enough to enable characterisation of chloroquine accumulation in this organelle in terms of time-, temperature-, Mg²⁺-, pH-, ATP- and other nucleotide-dependence. The chloroquine accumulating capabilities of vacuoles isolated from chloroquine-resistant and chloroquine-sensitive parasites were compared. At an external chloroquine concentration of 100 and 250nM vacuoles isolated from two chloroquine-sensitive strains accumulated significantly more chloroquine (± 3 x) than those isolated from three of the four chloroquine-resistant strains of Plasmodium falciparum tested. Although it is often suggested that the parasite digestive vacuole is involved in the mechanism of chloroquine-resistance, this is the first direct evidence to suggest this. Vacuolar proton pump inhibitors, proton gradient dissipaters, P-glycoprotein ATPase- and drug transport-inhibitors, weak bases, and structural analogues of chloroquine were used to examine the driving force of chloroquine accumulation in the isolated food vacuole. A pH gradient between the vacuole and cytoplasm is necessary to retain chloroquine in this organelle, but a chloroquine transport mechanism appears to be the main driving force in chloroquine accumulation. A polyclonal antibody directed at Pgh1, a Plasmodium falciparum homologue of P-glycoprotein, confirmed its presence on the vacuole, but was unable to inhibit chloroquine accumulation in isolated vacuoles. This thesis also shows that agents, such as verapamil, which are able to reverse chloroquine-resistance by increasing chloroquine accumulation in parasitised erythrocytes, are unable to increase chloroquine accumulation in the isolated vacuole, suggesting the involvement of an alternate site for the reversal of chloroquine-resistance.